2019
DOI: 10.1016/j.joto.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of parents and siblings of children with cochlear implants

Abstract: ObjectivesThis study examined the quality of life (QoL) of the parents and siblings of hearing-impaired children with cochlear implants (CIs).DesignThis is a cross-sectional, questionnaire-based study. The questionnaire consists of three sub-domains - interaction, emotional well-being and support for the hearing-impaired child and the overall QoL -- and two open-ended questions for participants to provide comments and suggestions to enhance their family's QoL. A total of 63 questionnaires were e-mailed or mail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…One sibling noted how problems in hearing could lead to arguments, whereas another sibling realized how HL could negatively influence the conversation process. This finding agrees with Umat et al (2019), who reported siblings assigned the most positive rating for interaction to the statement, "My sibling knows when I want his attention because he can hear me calling." Regardless of the exact issue faced by individual families, the sibling's assessment of their brother or sister with CIs seems clear: CI users demonstrate social communication deficits in real-world scenarios.…”
Section: Negative Aspects Of Having a Brother Or Sister With Cissupporting
confidence: 89%
See 4 more Smart Citations
“…One sibling noted how problems in hearing could lead to arguments, whereas another sibling realized how HL could negatively influence the conversation process. This finding agrees with Umat et al (2019), who reported siblings assigned the most positive rating for interaction to the statement, "My sibling knows when I want his attention because he can hear me calling." Regardless of the exact issue faced by individual families, the sibling's assessment of their brother or sister with CIs seems clear: CI users demonstrate social communication deficits in real-world scenarios.…”
Section: Negative Aspects Of Having a Brother Or Sister With Cissupporting
confidence: 89%
“…The previous studies included deaf or hard-of-hearing children who predominantly communicated orally, but the authors did not specify if the children used auditory technology such as hearing aids (HAs) and/or CIs. Umat et al (2019) completed the most comprehensive assessment of quality of life in the siblings with TH of children with HL who use a CI. Twenty-three siblings (12-17 years of age) from 44 families of children with CIs (3-11 years of age) completed a quality-of-life questionnaire.…”
Section: Quality Of Life and Life Satisfactionmentioning
confidence: 99%
See 3 more Smart Citations